2011
DOI: 10.1038/onc.2011.577
|View full text |Cite
|
Sign up to set email alerts
|

SULF2 methylation is prognostic for lung cancer survival and increases sensitivity to topoisomerase-I inhibitors via induction of ISG15

Abstract: The heparan sulfate 6-O-endosulfatase (SULF2) promotes growth and metastasis of solid tumors. We recently identified that cytosine methylation of the SULF2 promoter is associated with better survival of resected lung adenocarcinoma patients and now also demonstrate a marginal improvement in survival of advanced non-small cell lung cancer (NSCLC) patients receiving standard chemotherapy (HR = 0.63, p = 0.07). Subsequent studies focused on investigating the effect of methylation on SULF2 expression and its genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…For another example, SULF2, an endosulfatase able to cleave specific 6-O sulfate groups within the heparan chains, was additionally identified to be hypomethylated in the Quantile-normalized data for colorectal, kidney and stomach cancer. It was found that SULF2 was over-expressed in various human cancer types and associated to cancer progression and prognosis (Bret et al, 2011;Lemjabbar-Alaoui et al, 2010;Tessema et al, 2011). These important cancer related genes identified by Quantile normalization suggested the effectiveness of this normalization algorithm on identifying DM genes.…”
Section: Effects Of Normalization On Methylation Data Signalsmentioning
confidence: 96%
“…For another example, SULF2, an endosulfatase able to cleave specific 6-O sulfate groups within the heparan chains, was additionally identified to be hypomethylated in the Quantile-normalized data for colorectal, kidney and stomach cancer. It was found that SULF2 was over-expressed in various human cancer types and associated to cancer progression and prognosis (Bret et al, 2011;Lemjabbar-Alaoui et al, 2010;Tessema et al, 2011). These important cancer related genes identified by Quantile normalization suggested the effectiveness of this normalization algorithm on identifying DM genes.…”
Section: Effects Of Normalization On Methylation Data Signalsmentioning
confidence: 96%
“…9 In NSCLC, SULF2 and IGFBP-3 have also been observed to affect drug sensitivity of NSCLC cells. [10][11][12] The HOX family, including 39 HOX genes, is divided into four groups (A-D) in tightly linked clusters on different chromosomes, and has the equivalent position in each cluster. HOXA1, one of the HOX family members, has been reported to be involved in many important biological processes including cell growth, apoptosis, transformation, and survival.…”
mentioning
confidence: 99%
“…Expression of CCDC37 , MAP1B, and BETA-ACTIN was quantified using Hs00403623_m1, Hs00195485_m1, and 4310881E TaqMan assays (Applied Biosystems), respectively, as described. 24,25 All samples were analyzed at least twice in duplicate and expression levels were calculated using ΔΔCT method. 26 …”
Section: Methodsmentioning
confidence: 99%